2018
DOI: 10.1002/jpln.201700246
|View full text |Cite
|
Sign up to set email alerts
|

Considerations on cross‐linking by bivalent cations in soil organic matter with low exchange capacity

Abstract: A soil's cation exchange capacity (CEC) is expected to be relatively inert against changes in cation loading. In this study, we treated a soil sample originating from the organic layer of a forest soil with various bivalent cations after removing the native cations. Sorption isotherms and cation exchange capacity were determined, the latter using the BaCl2 method. Sorption showed Langmuir characteristics, with the maximum coverage (Qmax) increasing in the order Ba2+ < Ca2+ < Mg2+, but being clearly smaller tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…The soil sample and the procedure for cation treatment are described in detail in the first part of this article series ( Schaumann and Kunhi Mouvenchery , ). Briefly, the soil sample was collected from an organic surface layer of a Haplic Podzol (pH = 3.8, CEC = 303 ± 23 mmol c kg −1 ), sampled in a forest stand dominated by 80 year old Norway spruces ( Picea abies L.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The soil sample and the procedure for cation treatment are described in detail in the first part of this article series ( Schaumann and Kunhi Mouvenchery , ). Briefly, the soil sample was collected from an organic surface layer of a Haplic Podzol (pH = 3.8, CEC = 303 ± 23 mmol c kg −1 ), sampled in a forest stand dominated by 80 year old Norway spruces ( Picea abies L.…”
Section: Methodsmentioning
confidence: 99%
“…This contribution is the second part of a series addressing the reactions of an organic forest soil sample on the treatment with earth alkaline cations after removal of the original cations. The first part ( Schaumann and Kunhi Mouvenchery , ) showed that the treatment cations sorbed to the organic matter follow a Langmuir model with Langmuir coefficients ( k Me ) increasing in the order k Mg < k Ca < k Ba . Furthermore, the cation exchange capacity estimated by the BaCl 2 method unexpectedly varied with the amount and type of cations present in the soil sample.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations